Residual stress distribution and elevated temperature fatigue behaviour of laser peened Ti-6Al-4V with a curved surface - Praveenkumar, K.; Mylavarapu, Phani; Sarkar, Aritra; Isaac Samuel, E.; Nagesha, A.; Swaroop, S. (International journal of fatigue, 2022)
•Residual stress distribution was investigated in curved samples of laser peened Ti-6Al-4V.•Elevated temperature (300 °C) fatigue tests were done (R = −1) on similar curved samples.•Induced residual stress distribution was favorably retained at elevated temperature.•Crack initiation site shifted to a depth of ∼ 200 μm with 3 times increase in fatigue life at 400 MPa for the peened samples.•Fatigue striation spacings decreased for the peened samples. The influence of laser shock peening without coating (LPwC) on the induced compressive residual stress and the fatigue behaviour (R = −1 at 300 °C) was investigated on curved samples of Ti-6Al-4V. The stress relaxation after fatigue was also examined. In the peened samples crack initiation shifted to a depth of ∼ 200 μm, with 3 fold increase in fatigue life at 400 MPa. Decrease in fatigue striations in the laser peened (331.48 nm/cycle) samples compared to unpeened (410.54 nm/cycle) samples indicated retardation of crack propagation rate. Further, the effect of grain refinement and misorientation angles on fatigue behaviour is also considered.